The State’s responsibility to support indebted final year health sciences students in South Africa - Matlala, Kgopelo (My University, 2022)
In this study, I analyse the ethical challenge faced by indebted healthcare students in South Africa of not being able to graduate and enter community service. The number of indebted healthcare students who are not able to enter community service is often under-reported. However their failure to pay off these fees results in them not being able to graduate. The State has provided NSFAS loans for students whose families earn a household income of R350 000. Those who earn more than R350 000 would not qualify, causing healthcare students in the “Missing Middle” being unable to pay their tuition in time to graduate. This results in the shortage of healthcare professionals entering community service that is required for an adequate public healthcare system. In this report, I examine legal framework and ethical theories aimed at improving the status of healthcare, to make a case that the State has an ethical obligation to assist these students, all things considered. Through the ethical theories of Rule Utilitarianism, Weber’s Stewardship model, the Common Good approach, Rawls’ Theory of Justice and the Difference Principle, I present arguments which show that 1) the current status quo is ethically problematic, 2) the State rather than any other entity is best equipped to address, 3) the State providing loans is the most ethically appropriate option for assistance and 4) this obligation on the State to provide loans to these students outweighs all other competing claims on the State coffers. All things considered, the State has an ethical obligation to assist these indebted healthcare students.
A research report submitted in partial fulfilment for the degree of Master of Medicine in Bioethics and Health Law to the Faculty of Health Sciences, School of Clinical Medicine University of the Witwatersrand, Johannesburg, 2022